Iran : the nuclear challenge - Abrams, Elliott, 1948-; Blackwill, Robert D. (Council on Foreign Relations, 2012)
Iran: The Nuclear Challenge maps the objectives, tools, and strategies for dealing with one of the most vexing issues facing the United States and global community today. The book brings together leading experts-CFR's Elliott Abrams, Robert D. Blackwill, Robert M. Danin, Richard A. Falkenrath, Matthew Kroenig, Meghan L. O'Sullivan, and Ray Takeyh-on the issues and contingencies surrounding Iran's nuclear program, including sanctions, negotiations, U.S. and Israeli military options, regime change, and how to deal with a latent or actual Iranian nuclear weapons capability. This volume presents one of the clearest pictures of Iran's nuclear program to date, along with the various policy options available to the United States and others and their potential consequences.